Demographic characteristics and ocular needs of children attending child eye clinics in Cross River State, Nigeria: a retrospective analysis of clinical records - Nathan Congdon; Ciaran O'Neill; Lynne Lohfeld; Ving Fai Chan; Diarmuid O’Donovan; Ai Chee Yong; Christine Graham; Anne Effiom Ebri; Sara E O’Connor (BMJ Open)
Objectives To describe the demographic characteristics and ocular needs of children attending four child eye clinics in Cross River State, Nigeria, to inform the development of a sustainable spectacle cross-subsidisation scheme.Design Retrospective analysis of clinic records.Setting Four child eye clinics in Calabar, Ogoja, Ikom and Ugep, Cross River State, Nigeria, from 1 May 2017 to 30 June 2019.Participants Children who failed the vision screening in schools and visited assigned child eye clinics, and self-referred children from the community.Main outcome measures Children’s age, sex, residence, diagnosis, disease management, presenting and corrected visual acuity, history of spectacle wear and magnitude of refractive errors in spherical equivalent in the worse eye.Results Of all the 3799 records reviewed, data were available for 3774 children (mean age 10.6±4.35 years; 61.6% girls; 69.1% from urban settings); 30.8% (n=1162) of them had vision impairment. Of those children, 71.2% (n=827) were diagnosed with refractive error. For management, 48.6% (n=1833) were prescribed spectacles and 40.5% (n=1527) were prescribed ocular medications. Children prescribed spectacles were significantly more likely to be girls (68.0%, p<0.001), and older than 13 years of age (53.6%, p<0.001). The most common range of spherical equivalent (in the worse eye) was <−0.50 DS to +1.75 DS (51.6%, n=945), followed by >−0.25 DS to −3.00DS (39.7%, n=727). Non-refractive eye conditions such as cataract (33.3%) and corneal disorders (14.1%) contributed to almost half of the total blindness.Conclusion The findings show that spectacles provisions and ocular medications are the primary and secondary needs for children who attended child eye clinics seeking eye care services. Further research is needed to understand parents’ willingness to pay for spectacles to set strategic multitier pricing for a sustainable cross-subsidisation scheme.